Hydropower operation in future power grid with various renewable power integration. (December 2022) - De Silva, Thushara; Jorgenson, Jennie; Macknick, Jordan; Keohan, Nicholas; Miara, Ariel; Jager, Henriette; Pracheil, Brenda
Highlights: The study aims to understand the role of hydropower in a changing U.S. power grid with increasing levels of renewable using a production cost model. Hydropower dispatch follows the net load pattern in all seasons providing higher ramping to compensate for VRE generation variability. Hydropower revenue is sensitive to regional VRE contribution levels and hydrologic variation, and higher revenue potential by supplying various grid services. Flexible hydropower operation with variable capacity factors and increased ramping noted in results might not be feasible with other water use and environmental constraints. Abstract: Hydropower generation may play an increasingly important role in the power grid under increasing contribution of variable renewable sources such as wind and solar. An improved understanding of the changes to hydropower dispatch under future higher VRE grid conditions reveals research gap that should be informed power grid planning and reservoir water releases policies considering multiple other water uses and varying hydrologic condition. This study aims to understand the role of hydropower in a changing power grid by employing a production cost model, PLEXOS, across future power system scenarios, planning horizons, and regions. We explore optimized hydropower dispatch to understand its potential role in minimizing the system cost and renewable curtailment. We also examine the sensitivity of hydropower revenue under various grid scenarios of the Eastern U.S. and hydrology conditions. Results indicate hydropower generation follows net load and compensates for the variability of solar and wind generation. Although energy prices are lower during some periods in the future grid scenarios, there is a potential for higher revenue for hydropower by providing both energy and ancillary services during times of stress. Further, hydropower revenue is sensitive to hydrology in the SERC region, which we considered as an example. The feasibility of hydropower dispatching with higher ramps between low and high hourly-capacity factors, as indicated in the optimization model, requires further study to consider other water use and ecology constraints.